Menganalisis Kasus Ronald Tannur 2023 Terhadap Hukum dan HAM - Zai, Heni Erlita Sari; Dachi, Claudia Sri Rahayu Pertiwi; Samonaha Hia, Julius Aplikasi; Mardliyah, Ainul; Naibaho, Juan Lastio; Benedick P.S, Henry; M, Mulyadi (Media Hukum Indonesia (MHI), 2025)
Our purpose in analyzing this case is aligned with the theme of "Violations of Law and Human Rights in Indonesia." This serves as the foundation for our selection of this case, with the aim that through discussion and awareness of legal and human rights violations, particularly within the scope of femicide in Indonesia, we can contribute to addressing this issue. As university students, we hope that cases of legal and human rights violations, including femicide, will decrease over time following the publication of this journal. The method we use in analyzing the Ronald Tanur case is a literature-based approach